2019
DOI: 10.1101/630921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An epigenetic landscape governs early fate decision in cellular aging

Abstract: Chromatin instability and mitochondrial decline are conserved processes that contribute to cellular aging. Although both processes have been explored individually in the context of their distinct signaling pathways, the mechanism that determines which cell fate arises in isogenic cells is unknown. Here, we show that interactions between the chromatin silencing and mitochondrial pathways lead to an epigenetic landscape with multiple equilibrium states that represent different types of terminal cellular states. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Similarly, the likelihood that a GLM will be properly resolved in a given mother cell once it occurs also appears to be variable and under genetic control. Other recent studies have indicated that aging yeast cells can experience different trajectories or ‘modes’ of aging, as indicated by expression of reporter genes that differ within sub-populations of cells (Crane and Kaeberlein, 2018; Jin et al, 2019; Li et al, 2019). This raises the interesting possibility that not all cells experience the same age-related genome instability, perhaps due to stochastic or inherited factors that influence early life cell fates (Li et al, 2019; Morlot et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the likelihood that a GLM will be properly resolved in a given mother cell once it occurs also appears to be variable and under genetic control. Other recent studies have indicated that aging yeast cells can experience different trajectories or ‘modes’ of aging, as indicated by expression of reporter genes that differ within sub-populations of cells (Crane and Kaeberlein, 2018; Jin et al, 2019; Li et al, 2019). This raises the interesting possibility that not all cells experience the same age-related genome instability, perhaps due to stochastic or inherited factors that influence early life cell fates (Li et al, 2019; Morlot et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies have indicated that aging yeast cells can experience different trajectories or ‘modes’ of aging, as indicated by expression of reporter genes that differ within sub-populations of cells (Crane and Kaeberlein, 2018; Jin et al, 2019; Li et al, 2019). This raises the interesting possibility that not all cells experience the same age-related genome instability, perhaps due to stochastic or inherited factors that influence early life cell fates (Li et al, 2019; Morlot et al, 2019). Intriguingly, in the Jin, et al study, they identified two aging paths and cells that died from the second path experienced a reduced mean lifespan, but a similar maximal lifespan to those that died from the first path.…”
Section: Discussionmentioning
confidence: 99%